Prediksi Arus Kas Bebas, Kebijakan Utang, dan Profitabilitas terhadap Kemungkinan Dibayarkannya Dividen: Studi Empirik pada Emiten Pembentuk Indeks Kompas 100 di Bursa Efek Indonesia - Hadianto, Bram; Herlina, Herlina (International Research Journal of Business Studies, 2010)
The aim of this research is to know the prediction of some explanatory factors that impact on probability of public company to divide earnings to investor and find the accuracy rate to classify public company become two group based on some explanatory factor. First group is dividend payer’s company, and second group is non-dividend payer’s company. Some explanatory factors that we used are free cash flow, debt policy, and profitability. We employ logistic regression model as data analysis method. Our sample is taken from the Kompas 100 Index constituent public company in 2007. The results point out both debt policy and profitability are positively relationship with dividend policy and free cash flow has no significant relationship with dividend policy. In addition, the accuracy of all factors that used to classify both dividend payer’s company group and dividend non-payer’s company group are 69%.